On the Limitation of Telegrapher's Equations for Analysis of Nonuniform Transmission Lines - 김세윤 (한국전자파학회, 2004)
The limitation of telegrapher's equations for analysis of nonuniform transmission lines is investigated here. It is shown theoretically that the input impedance of a nonuniform transmission line cannot be derived uniquely from the Riccati equation only except for the exponential transmission line of a particular frequency-dependent taper. As an example, the input impedance of an angled two-plate transmission line is calculated by solving the telegrapher's equations numerically. The numerical results suffer from larger deviation from its rigorous solution as the plate angle increases.